The Effect of Beauty Influencer Credibility and Electronic Word Of Mouth on Purchase Intention Skintific Skincare Products Through Customer Trust Variable - Farahsalsabil Yudhiane Cantika; Nurhadi Nurhadi (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to examine the impact of Tasya Farasya’s credibility as a beauty influencer and electronic word of mouth (E – WOM) on purchase intention through by consumer trust in Skintific skincare products in Surabaya. This study uses quantitative methods. The population of this study is a consumer of Skintific skincare products in Surabaya. The sample size was 150 respondent was taken using purposive sampling. Data collection techniques use quesionnaires distributed through Whatsapp, Instagram, and Twitter. The analysis techniques uses Partial Leas Square (PLS) with SmartPLS 4.0 software. The result showed that credibility of beauty influencers and electronic word of mouth significantly affect purchase intention. Credibility of beauty influencers does not significantly affect purchase intention. Electronic word of mouth has affect but not significantly purchase intention. Customer trust significantly affect purchase intention. Beauty influencer credibility has a significant indirect effect on purchase intention through consumer trust, while electronic word of mouth also has a significant indirect effect on purchase intention through consumer trust.